2013
DOI: 10.1089/bio.2013.0023
|View full text |Cite
|
Sign up to set email alerts
|

Permission to Contact (PTC)—A Strategy to Enhance Patient Engagement in Translational Research

Abstract: A PTC platform is a feasible mechanism to engage patients in research programs such as biobanking. It is well supported by clinic staff and receives high engagement and acceptance from patients. Patient-approach rates vary in different clinics, likely due to both clinic and PTC process factors, but this strategy provides an efficient means of engaging patients in research and sets the stage for enhanced enrollment into translational research programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 5 publications
2
20
0
Order By: Relevance
“…Another strategy for a tumor biobank is to refocus enrolment energy into obtaining consent for biobanking from representative populations diagnosed with cancer, independent of the likelihood of being able to secure fresh or frozen materials at the time of surgery. 12 This facilitates enacting processes to access to FFPE materials in the clinical pathology archives. Active utilization of population-based cancer registries can identify specialized potential cohorts associated with clinical FFPE biospecimens, for example, cohorts with biospecimens that span clinical events and that can be linked by a dedicated effort by the biobank to compile the cohort for researchers.…”
Section: Figmentioning
confidence: 99%
“…Another strategy for a tumor biobank is to refocus enrolment energy into obtaining consent for biobanking from representative populations diagnosed with cancer, independent of the likelihood of being able to secure fresh or frozen materials at the time of surgery. 12 This facilitates enacting processes to access to FFPE materials in the clinical pathology archives. Active utilization of population-based cancer registries can identify specialized potential cohorts associated with clinical FFPE biospecimens, for example, cohorts with biospecimens that span clinical events and that can be linked by a dedicated effort by the biobank to compile the cohort for researchers.…”
Section: Figmentioning
confidence: 99%
“…We have shown that when this ''Permission to Contact'' platform is shared by several biobanks and clinical research projects in a center or region there can be many benefits including enhanced enrollment and reduced overall cost of consent. 27,28 As noted above, there is significant and largely unrecognized diversity in types of biobanks. The small-and medium-sized mono-and oligo-user biobanks comprise the majority of biobanks, and are typically designed to address specific research questions.…”
Section: Operational Dimensionmentioning
confidence: 99%
“…This is one of the benefits for a biobank of implementing a ''permission to contact'' platform as a separate process in addition to operating the other components of its own existing consent mechanism. 27,28 The ''permission to contact'' serves the biobank itself but also provides another distinct product to researchers, either alone or in conjunction with a banked biospecimen. Similarly, adoption of the Biospecimen Reporting for Improved Study Quality (BRISQ) guidelines, 29 which is required or recommended by some journals such as Nature, is made easier to accomplish by the use of an online tool offered by the BRC.…”
Section: Operational Dimensionmentioning
confidence: 99%
“…To address issues regarding initial access to patients and biobank donation, some groups have demonstrated the success of 'Permission to Contact' models, under which all patients who present for care in a clinical setting are approached to request consent that they be contacted at a later date regarding future research opportunities. This method has the potential to dramatically improve the number of suitable participants available for biobank initiatives (80-94 % of those approached agree to be contacted), while at the same time increasing research potential with improved access to eligible patients, which is essential for the 'big data' science now being demanded to accurately characterize and validate biomarkers (Cheah et al 2013).…”
Section: Consentmentioning
confidence: 99%